Early effects of the COVID-19 lockdown on children in rural Bangladesh - Momoe Makino; Abu Shonchoy; Zaki Wahhaj (University of Kent, School of Economics, 2021)
Using data collected through a telephone-based survey in rural Bangladesh during the height of the pandemic, we present evidence on the effects of COVID-19-led lockdown and school closures on children, focusing on three child-related outcomes: time use of children during the school closure, plans regarding children's schooling continuation, and the incidence of child marriages. Our analysis reveals heterogeneity in the effects of lockdown and school closure in terms of the child's gender and the type of shocks. We find a decrease in children's study time and an increase in time spent on household chores during the school closure, and these changes were significantly larger for girls than for boys. Within the household, respiratory illness lowered expectations that a child would return to school and increased the probability of marriage-related discussions for girls. Our findings offer a cautionary tale regarding the potential longterm effects of pandemic for girls in developing countries.
Keywords: I25; J12; O53; 330; COVID-19; school closure; child marriage; children's time allocation; Bangladesh